Mahar Politik pada Pengusungan Kandidat Pemilihan Umum Kepala Daerah di Kabupaten Bolaang Mongondow Selatan dalam Perspektif Hukum Islam - Kasman Bakry; Ihwan Wahid Minu; Novia Amalia Safitri (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2022)
This study aims to determine the perspective of Islamic law on political dowry involving political parties and regional head general election candidates. This study use a type of qualitative research (non-statistical) which focuses on field research (field research) using a normative and phenomenological approach. Data processing and analysis techniques refer to the interactive model concept, which is a concept that clarifies data analysis in behavioral steps, including data reduction, data presentation and drawing conclusions. Political dowry actually happened and is something that is forbidden because it is equivalent to risywah or bribery. The results of this research can be a source of knowledge and material for reflection for those who want to be part of the leadership of a region in a vanity way so that the value of honesty will be given more attention to maintain the stability of democracy.